The effects of pituitary and thyroid disorders on haemostasis: potential clinical implications. (27th March 2015) - Kyriakakis, Nikolaos; Lynch, Julie; Ajjan, Ramzi; Murray, Robert D.
Summary: Disturbances of coagulation and fibrinolysis are usually multifactorial and growing evidence suggests that endocrinopathies modulate the haemostatic balance. The thrombotic alterations in endocrine disorders range from mild laboratory clotting abnormalities with little clinical significance to serious thrombotic and bleeding disorders directly related to hormonal disturbances. This literature review focuses on presenting the current data on the effects of thyroid and pituitary disorders on various parameters of the haemostatic system. With the exception of overt hypothyroidism which appears to cause a bleeding tendency, the rest of the endocrinopathies discussed in this review (subclinical hypothyroidism, hyperthyroidism, endogenous hypercortisolaemia, growth hormone deficiency, acromegaly, prolactinoma/hyperprolactinaemia and hypogonadotrophic hypogonadism) are associated with a hypercoagulable and hypofibrinolytic state, increasing the overall cardiovascular risk and thromboembolic potential in these patients. In most studies, the haemostatic abnormalities seen in endocrine disorders are usually reversible with successful treatment of the underlying condition and biochemical disease remission. High‐quality studies on larger patient cohorts are needed to produce robust evidence on the effects of endocrine disorders and their therapeutic interventions on coagulation and fibrinolysis, as well as on the long‐term mortality and morbidity outcomes in association with endocrine‐related haemostatic imbalance. Given the rarity of some of the endocrine disorders, multicentre studies are required to achieve this target.